2018
DOI: 10.3899/jrheum.170516
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Medication Pattern Change of Psoriatic Diseases in Taiwan from 2000 to 2013: A Nationwide, Population-based Cohort Study

Abstract: The prevalence and incidence rates of psoriatic disease, especially PsA, were increasing in Taiwan. The medication pattern showed an increase in DMARD and biologics, while use of topical therapies decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
5
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 26 publications
10
33
5
3
Order By: Relevance
“…The discrepancy could also be explained by over-representation of the more severe early-onset presentation in studies of highly selected populations. 7,22,24 Our results suggest increased incidence and prevalence rates of psoriasis among men, compared to women, in line with some, [30][31][32] but not all previous reports. 27,28 However, the absolute magnitude of the sex difference is small, and its clinical implications are therefore questionable.…”
Section: Interpretation Of the Findings And Comparison With Existing supporting
confidence: 89%
See 1 more Smart Citation
“…The discrepancy could also be explained by over-representation of the more severe early-onset presentation in studies of highly selected populations. 7,22,24 Our results suggest increased incidence and prevalence rates of psoriasis among men, compared to women, in line with some, [30][31][32] but not all previous reports. 27,28 However, the absolute magnitude of the sex difference is small, and its clinical implications are therefore questionable.…”
Section: Interpretation Of the Findings And Comparison With Existing supporting
confidence: 89%
“…Recent studies showed that the average incidence of psoriasis per 100 000 person‐years ranged between 38 new cases in Taiwan, new cases in Canada, in Denmark, in the UK and 230–320 in Italy . The substantially higher incidence rate in CHS could reflect the high accessibility of dermatological consultations (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of psoriasis was higher in adults than in children, varying from 30.3 per 100 000 person years (95% confidence interval 26.6 to 34.1)22 in Taiwan to 321.0 per 100 000 person years in Italy 23. While the data show a steadily increasing trend in incidence of psoriasis in adults in the US between 1970 and 2000 (table 2),24 data from Canada, Italy, and Taiwan show a slightly decreasing trend in incidence over time 222325…”
Section: Resultsmentioning
confidence: 94%
“…Рост распространенности псориаза на фоне стабильной заболеваемости отмечен в Тайване на протяжении 2000-2013 гг. [10], а также в Израиле в течение 2011-2017 гг. [11].…”
Section: %unclassified